2021
DOI: 10.1021/acsami.1c13534
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Oxygen Intake/Release Characteristics of Brownmillerite-Type Ca2AlMnO5+δ Involving Atomic Defect Formations

Abstract: The oxygen intake/release characteristics were systematically studied for Ca2AlMnO5+δ samples synthesized under precisely controlled oxygen pressures. Both the oxygen storage capacity (OSC) and operating temperature were systematically lowered as the oxygen pressure in the firing atmosphere increased. Notably, the sample fired under a 1% O2 atmosphere exhibited sufficiently large OSC and superior oxygen intake/release kinetics to the pristine sample synthesized in an anaerobic condition. The high-angle annular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…From the isothermal TG data, theoretical values of the daily O 2 -gas productivity were estimated for Ba 4 CaFe 3 O 9.5 and Ba 5 CaFe 4 O 12 , together with some representative OSMs reported in the literature (see Figure and Table S5). The values were calculated based on the amount of oxygen reversibly stored and released during the isothermal TG run, with the reaction time required for a single TG cycle . The Ba 4 CaFe 3 O 9.5 and Ba 5 CaFe 4 O 12 materials in the present study mark record-high values of the O 2 -gas production rate of >2.4 m O2 3 kg OSM –1 day –1 .…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…From the isothermal TG data, theoretical values of the daily O 2 -gas productivity were estimated for Ba 4 CaFe 3 O 9.5 and Ba 5 CaFe 4 O 12 , together with some representative OSMs reported in the literature (see Figure and Table S5). The values were calculated based on the amount of oxygen reversibly stored and released during the isothermal TG run, with the reaction time required for a single TG cycle . The Ba 4 CaFe 3 O 9.5 and Ba 5 CaFe 4 O 12 materials in the present study mark record-high values of the O 2 -gas production rate of >2.4 m O2 3 kg OSM –1 day –1 .…”
Section: Resultsmentioning
confidence: 84%
“…The Ba 4 CaFe 3 O 9.5 and Ba 5 CaFe 4 O 12 materials in the present study mark record-high values of the O 2 -gas production rate of >2.4 m O2 3 kg OSM –1 day –1 . These values are indeed much higher than 0.81 m O2 3 kg OSM –1 day –1 for Sr 0.76 Ca 0.24 FeO 3−δ operating at 550 °C and 0.99 m O2 3 kg OSM –1 day –1 for the “modified” Ca 2 AlMnO 5+δ operating at 472 °C . It is worth pointing out that the Ba–Ca–Fe oxides can work at temperatures below 400 °C, much lower than those for the reference OSMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2 AlMnO 5 + δ (CAMO) is one of the prominent OSM candidates other than Fe-based perovskites. CAMO is capable of storing and releasing up to 3.3 wt% of oxygen (Δδ = 0.5) according to the following oxygen storage/ release reaction: 14,15) Ca AlMnO + 2 O Ca AlMnO Although various studies on CAMO as the OSM have been reported so far, 14,[16][17][18][19][20][21][22] the HT-PSA test results of CAMO have not been reported. The HT-PSA test can reveal issues that do not manifest in individual characteristic studies, such as the oxygen storage and release reaction rates, which are not taken into account in equilibrium composition measurements, and the temperature change of the OSM owing to reaction heat, which is controlled during thermogravimetric measurements.…”
Section: Oxygen Separation Performance Of Ca 2 Almno 5 + δ As An Oxyg...mentioning
confidence: 99%